2004
DOI: 10.1039/b406378c
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrothermal conditions on the mesoporous structure of TiO2 nanotubes

Abstract: A systematic analysis of the influence of preparation conditions in the alkali hydrothermal synthesis on the morphology of TiO 2 nanotubes is performed using HRTEM and low temperature nitrogen adsorption. The possible mechanisms of nanotube formation are reviewed and a mechanism based on the key stage of wrapping of intermediate multilayered titanate nanosheets is suggested. The driving force for wrapping is considered to be the mechanical stress arising during crystallisation/dissolution. The average diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
515
3
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 701 publications
(568 citation statements)
references
References 34 publications
34
515
3
16
Order By: Relevance
“…1, the surface areas (197-312 m 2 g À1 ) and outer diameters of the TNs (5-13 nm) increased with the rising of heating temperature. However, for TN (180-2), the tubular structure disappeared, and nanosized fibers formed instead, which was consistent with the results reported by Lee et al [22], Yuan and Su [23] and Bavykin et al [24]. XRD results of TP showed that the raw material was a mixture of rutile and anatase (Fig.…”
Section: Characterization Of Protonated Tns and Tpsupporting
confidence: 82%
“…1, the surface areas (197-312 m 2 g À1 ) and outer diameters of the TNs (5-13 nm) increased with the rising of heating temperature. However, for TN (180-2), the tubular structure disappeared, and nanosized fibers formed instead, which was consistent with the results reported by Lee et al [22], Yuan and Su [23] and Bavykin et al [24]. XRD results of TP showed that the raw material was a mixture of rutile and anatase (Fig.…”
Section: Characterization Of Protonated Tns and Tpsupporting
confidence: 82%
“…Nowadays, TiO 2 nanotubes are synthesized by several methods, including sol-gel transcription [16,17], hydrothermal processes [18,19] and anodization of titanium in fluoride-based electrolytes [20,21]. The latter is the most promising because it allows obtaining highly ordered nanotube arrays, and their dimensions (length, diameter, and tube wall) can be precisely controlled [22].…”
Section: Introductionmentioning
confidence: 99%
“…The growing mechanism of BaTiO 3 nanotubes is similar to the formation of TiO 2 nanotubes. 23 The high-resolution TEM image ( Figure S1a of the Supporting Information) reveals d spacing of 0.28 nm for adjacent lattice fringes, which corresponds to the (110) crystalline plane of tetragonal BaTiO 3 .…”
mentioning
confidence: 99%